Unravelling: Photographic Explorations Of Mending The Forest - Pretorius, Emme (Michaelis School of Fine Art, 2024)
Unravelling: Photographic Explorations of Mending the Forest explores aspects of South Africa's Garden Route Afrotemperate forests and my relationship to them through my artistic practice. This project looks at the unravelling of these forests and at my unravelling within these forests and my artistic process. It is concerned with the coming undone of these forests' intricate systems in the interest of the Capitalocene, and with my figurative artistic attempts to fix these forests. This project further aims to make this unravelling visible, to indicate the faded and fragmented state of these forests. It also addresses the futility of some of the attempts to rectify the damage done to these forests. This document explores the importance of process and materiality in photography and in my artistic practice. Through the experimental use of darkroom processes, expired paper and the sewing of fragmented photographs, I aim to demonstrate how such processes and attention to materiality can make my practical and theoretical concerns visible.